Experimental Investigation of a Novel Condensing Boiler - ABDULKARIM, Ali H.; ALTINIŞIK, Kemal; ATEŞ, Ali; CANLI, Eyüb (International Journal of Computational and Experimental Science and Engineering, 2017)
A novel laboratory type condensing boiler was developed and a data acquisition system was set up in order to measure physical magnitudes related to the performance of the developed boiler. A closed circuit water circulation system was included in the experimental setup in order to circulate water as the energy carrier fluid. The boiler was operated according to the predetermined parameters and data acquisition system collect the data from electronic transmitters placed in the probes at the certain points in the experimental setup. All these results were presented in graphical form and they are interpreted in terms of physics related to the phenomena. The temperature increase in the boiler changes in a parabolic manner. At the beginning of the incident, convection dominantly occurs in respect of heat transfer even though radiation also exists. However radiation contributes more with elapsed time in the experiment and temperature rise curve deviates from the linear path. Numerical analyses can contribute to the findings as well as design parameters.